2021
DOI: 10.1111/ppc.12957
|View full text |Cite
|
Sign up to set email alerts
|

The effects of emotional freedom techniques on coping with premenstrual syndrome: A randomized control trial

Abstract: Purpose The present study evaluated the efficacy of Emotional Freedom Techniques (EFT), commonly called “tapping,” for premenstrual (PMS) symptoms. Design and Methods This study was conducted with the participation of 50 nursing students who scored 111 or higher on the Premenstrual Syndrome Scale (PMSS). The students in the experimental group were instructed to apply EFT. Findings There were statistically significant differences between the mean depressive affect, fatigue, nervousness, sleep‐related changes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A review of the literature revealed that few studies investigated the effect of EFT on family caregivers of patients. However, some studies reported the positive effect of this new technique on anxiety and stress,[ 24 ] cancer-related cognitive disorders,[ 35 ] menstrual-related symptoms,[ 36 ] depression,[ 26 ] fatigue,[ 37 ] and physiological indicators, such as blood pressure, heart rate, and cortisol. [ 38 ] Nevertheless, a review of the literature yielded that most of the interventions used to reduce the physical and psychological stress of family caregivers of patients with cardiovascular diseases, especially HF, resorted to psychological education and few studies addressed the effect of these techniques on family caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature revealed that few studies investigated the effect of EFT on family caregivers of patients. However, some studies reported the positive effect of this new technique on anxiety and stress,[ 24 ] cancer-related cognitive disorders,[ 35 ] menstrual-related symptoms,[ 36 ] depression,[ 26 ] fatigue,[ 37 ] and physiological indicators, such as blood pressure, heart rate, and cortisol. [ 38 ] Nevertheless, a review of the literature yielded that most of the interventions used to reduce the physical and psychological stress of family caregivers of patients with cardiovascular diseases, especially HF, resorted to psychological education and few studies addressed the effect of these techniques on family caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Several psychotherapeutic modalities have been shown to be efficacious in the treatment of PMS and PMDD, [186][187][188][189] although the preponderance of evidence favors cognitive behavioral therapy (CBT). 190 One meta-analysis of randomized controlled trials including 5 trials utilizing CBT in women with PMS found significant reductions in symptoms of anxiety and depression, although the quality of the available studies was concluded to be low.…”
Section: Psychotherapiesmentioning
confidence: 99%
“…It is one of the most prevalent health issues among women under the age of 25 and a leading cause of temporary absences from school or job, which causes a sizable economic loss. It can occasionally be so severe that it interferes with daily activities (Qiu et al, 2016& Bakır et al, 2022. The prevalence of dysmenorrhea is relatively high worldwide.…”
Section: Significance Of the Studymentioning
confidence: 99%